Given the equatiion:
b = 0.26h - 18.85
Let's solve for h.
To solve for h, take the following steps:
Step 1.
Rearrange the equation:
0.26h - 18.85 = b
Step 2.
Add 18.85 to both sides:
0.26h - 18.85 + 18.85 = b + 18.85
0.26h = b + 18.85
Step 3.
Divide all terms by 0.26
![\begin{gathered} (0.26h)/(0.26)=(b)/(0.26)+(18.85)/(0.26) \\ \\ h=(b)/(0.26)+72.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x2fs7p5p8yd6qj81n2555nklpgt018c35v.png)
Let's simplify further:
![\begin{gathered} h=(1b)/(0.26)+72.5 \\ \\ h=(1)/(0.26)b+72.5 \\ \\ h=3.846b+72.5 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/u1ocb1r5tvtw2z7chqujzjvpa4ej89uqzf.png)
ANSWER:
h = 3.846b + 72.5